2020
DOI: 10.3389/fpls.2020.604690
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the GRAS Gene Family and Functional Identification of GmGRAS37 in Drought and Salt Tolerance

Abstract: GRAS genes, which form a plant-specific transcription factor family, play an important role in plant growth and development and stress responses. However, the functions of GRAS genes in soybean (Glycine max) remain largely unknown. Here, 117 GRAS genes distributed on 20 chromosomes were identified in the soybean genome and were classified into 11 subfamilies. Of the soybean GRAS genes, 80.34% did not have intron insertions, and 54 pairs of genes accounted for 88.52% of duplication events (61 pairs). RNA-seq an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 61 publications
5
36
0
Order By: Relevance
“…Under drought or salt stress, TaDEAD-box57-3B transgenic Arabidopsis plants showed higher germination rates, root lengths, fresh weights and survival rates; moreover, transgenic lines had significantly better growth and higher survival rates than the WT after cold treatment. Chlorophyll content was measured as a proxy for the degree of cellular injury, and MDA content was quantified as a measure of membrane lipid peroxidation ( Gunes et al, 2011 ; Hong et al, 2016 ; Wang T. T. et al, 2020 ; Chen et al, 2021 ). Proline, a common osmoprotectant, is a regulator of osmotic pressure to maintain plant homeostasis in responses to adverse conditions, and generally increases in response to abiotic stress ( Szekely et al, 2008 ; Su et al, 2020 ; Wang et al, 2021 ; Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under drought or salt stress, TaDEAD-box57-3B transgenic Arabidopsis plants showed higher germination rates, root lengths, fresh weights and survival rates; moreover, transgenic lines had significantly better growth and higher survival rates than the WT after cold treatment. Chlorophyll content was measured as a proxy for the degree of cellular injury, and MDA content was quantified as a measure of membrane lipid peroxidation ( Gunes et al, 2011 ; Hong et al, 2016 ; Wang T. T. et al, 2020 ; Chen et al, 2021 ). Proline, a common osmoprotectant, is a regulator of osmotic pressure to maintain plant homeostasis in responses to adverse conditions, and generally increases in response to abiotic stress ( Szekely et al, 2008 ; Su et al, 2020 ; Wang et al, 2021 ; Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was also found in soybean root GRAS genes; most GmGRAS genes in the PAT1 subfamily were at relatively high expression levels under saline and dehydration stresses while GmGRAS genes in the SCL3 subfamilies displayed distinct correlation patterns ( Wang et al, 2020a ). What’s more, functional identification of GmGRAS37 in the PAT1 subfamily indicated that GmGRAS37 can enhance drought and salt tolerance in transgenic plants by activating the expression of genes involved in abiotic stress responses ( Wang et al, 2020b ). Recent research reported cucumber GRAS genes in the five subfamilies were diversely expressed during low and high temperature, salinity, and exogenous phytohormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in transgenic tomato plants expressing SbNHX of Sorghum bicolor, the tonoplast Na + /H + antiporter was found to have an interactive relationship with the gene family of the cation/proton antiporter (CPA), such as SOS. This suggests that NHX proteins might assist the cation antiporters on the plasma membrane to excrete Na + from cells and, thus, enhance the salt resistance of plants; however, the mechanism of their interaction remains unclear (Palavalasa et al, 2017). Besides, decrease of Na + in cytoplasm could lead to cut down of ROS and alleviate of stress damages.…”
Section: Discussionmentioning
confidence: 99%